Ethical Leadership Affecting Performance Effectiveness of the Sub-District Headman and Village Headman in Wang Yang District Nakhon Phanom Province - Pudpong, Natcha; Aiyakorn, Samart; Udomkijmongkol, Chardchai (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Leader ethics is the heart of leadership because if the leader has ethics, it will help create and promote the ethical values of the organization. The values that leaders support will have a significant impact on the values of the organization. Because of this influence, leaders play an important role in creating an ethical climate in their organizations and setting good examples of ethics for others. Thus, the purposes of the study included the following: 1) To study the level of ethical leadership and performance effectiveness of the sub-district headmen and village headmen in Wang Yang District, Nakhon Phanom Province, 2) To compare the performance effectiveness of the sub-district headmen and village headmen in Wang Yang District, Nakhon Phanom Province according to the public opinions which were classified by the people’s different personal characteristics, and 3) To investigate the influences of ethical leadership on the performance effectiveness of the sub-district headmen and village headmen in Wang Yang District, Nakhon Phanom Province. Methodology: Obtained through a stratified random sampling method, the samples consisted of 388 people whose domiciles are in Wang Yang District, Nakhon Phanom Province; they are 18 years old or over. The questionnaire was used as a tool for collecting the data. Statistics employed for data analysis were frequency, percentage, mean, standard deviation, t–test, One–way ANOVA, and Multiple Regression Analysis. Results: (1) The overall ethical leadership of the sub-district and village headmen In Wang Yang District, Nakhon Phanom Province was at a high level. At the same time, their performance effectiveness was also at a high level. (2) based on their different residences, the performance effectiveness of the sub-district and village headmen in Wang Yang District, Nakhon Phanom Province, according to public opinions, varied. However, the performance effectiveness of the sub-district and village headmen in Wang Yang District, Nakhon Phanom Province did not differ according to their different genders, ages, educational levels, occupations, and monthly incomes. (3) Regarding the ethical leadership of the sub-district and village headmen, these aspects of their ethical leadership significantly influenced the performance effectiveness of the sub-district and village headmen in Wang Yang District, Nakhon Phanom Province at the .01 statistical level: caring for others (β=.418), ethical guidance (β=.377), long-term care (β=.270), honesty (β=.225), justice (β=. 192) and power-sharing (β=.124. Except for the clarity of their roles, these aspects could be used jointly to accurately predict the level of performance effectiveness of the sub-district and village headmen in Wang Yang District, Nakhon Phanom Province 65.00% (R2Ad=.650). Conclusion: The study underscores the positive correlation between high levels of ethical leadership and the effectiveness of sub-district and village headmen. Despite regional variations in performance based on residence, the absence of significant differences related to demographic factors suggests a consistent standard of effectiveness. The identification of specific ethical leadership qualities as significant predictors emphasizes the pivotal role played by attributes such as caring for others, ethical guidance, long-term care, honesty, justice, and power-sharing. This highlights the importance of cultivating these ethical dimensions to enhance the overall performance effectiveness of local leaders in Wang Yang District.